Spontaneous recanalization of the basilar artery with conservative management months after symptom onset - Joel M. Oster; Puja Aggarwal (Neurology International, 2009)
Basilar artery occlusion may be associated with a poor prognosis in the absence of recanalization. Choices in aggressive treatment for this potentially fatal condition vary from intra-arterial or intravenous thrombolysis, endovascular removal, or a combination of the two, with adjunct anti-coagulation therapy. These therapies have proven to be effective in recanalization, whereas conservative management with anti-coagulants alone has had more limited success in the literature. We report a case of basilar artery occlusion managed conservatively with unfractionated heparin, resulting in complete recanalization 3.5 months after symptom onset. Conservative management of basilar artery occlusion with unfractionated heparin was associated with complete recanalization long after symptom onset.